The Market-Socialist Country. Issue 6 (2nd June 2016) - Veselova, E.Sh.
Abstract : Over the past twenty years, Belarus has been building "market socialism" in the country under the continuous leadership of Alexander Lukashenko. By some socioeconomic indicators, Belarus appears better than its Eastern neighbors: the economy is growing more rapidly than Ukraine's, its structure is more balanced than Russia's. It has a high level of employment, relatively little social stratification, and modernized businesses in traditional industry. This does not mean that it is problem-free: the country has survived two crises in just the past five or six years. Nevertheless, it continues to chart its own course through the dark without looking to foreign advice.